The Role of Transaction Costs and Risk Premia in the Determination of Climate Change Policy Responses - Marcus Stronzik; Alistair Hunt; Frauke Eckermann; Tim Taylor (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
Transaction costs and risk have generally not been taken into account in assessing the Kyoto mechanisms JI, CDM and emissions trading. However, they can have a significant influence. With regard to the project-based mechanisms, the factor that most determines the influence of transaction costs on the implementation of a project is the size of the particular project. For some projects transaction costs amount up to over 1000 ?/ton C reduced, which proves the necessity of streamlining procedures, as recognised in the Marrakesh Accords. With regard to international emissions trading it will be of high importance to build on experience with past national emissions trading schemes in order to keep transaction costs low. However, international trading schemes of the type envisaged under the Kyoto Protocol are likely to have significant issues that have not been addressed in previous national experience. In addition to transaction costs, we determine country risk premia to account for the fact that projects in different states may induce different levels of risk of default or project failure.
Keywords: Q51; Q58; D52; 330; transaction costs; risk premia; Kyoto Protocol; emissions trading; small scale projects; Klimaschutz; Internationale Umweltpolitik; Clean Development Mechanism; Transaktionskosten; Risikoprämie; Entwicklungsprojekt; Welt